2020
DOI: 10.1039/d0qi01013h
|View full text |Cite
|
Sign up to set email alerts
|

Surface defect engineering of mesoporous Cu/ZnS nanocrystal-linked networks for improved visible-light photocatalytic hydrogen production

Abstract: Transition metal sulfides have been emerging as one of the most attractive and prospective catalysts for direct conversion of solar energy into chemical fuels. The intriguing compositional and electronic characteristics...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 75 publications
2
11
0
Order By: Relevance
“…Semiconductors nanoparticles (NPs) have found numerous applications in different technological fields going from photovoltaic devices to medical imaging, lasers, LEDs and photocatalysis (Dao 2020;Rtimi et al 2021;Meikle et al 2020;Long et al 2020;Su et al 2020;Li et al 2019;Daskalakis et al 2020;Rtimi et al 2021). These applications are supported by their unique properties as compared to their bulk counterpart, which arise from the confinement of the charge carriers as a result of their small sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductors nanoparticles (NPs) have found numerous applications in different technological fields going from photovoltaic devices to medical imaging, lasers, LEDs and photocatalysis (Dao 2020;Rtimi et al 2021;Meikle et al 2020;Long et al 2020;Su et al 2020;Li et al 2019;Daskalakis et al 2020;Rtimi et al 2021). These applications are supported by their unique properties as compared to their bulk counterpart, which arise from the confinement of the charge carriers as a result of their small sizes.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the nanoarchitecture altered the potential differences across the pore walls, where mesopores created spatial separation for charge carriers. The spatially separated carriers created along the mesopores are much lower, establishing a higher EFD as the pore size reduces, resulting in large domain boundaries in nanocrystalline materials [22, 33, 34] . The mobile carriers accumulated or trapped, which affected, and created a localized charge build‐up at domain boundaries that acted as carrier trapping/recombination sites.…”
Section: Resultsmentioning
confidence: 99%
“…The spatially separated carriers created along the mesopores are much lower, establishing a higher EFD as the pore size reduces, resulting in large domain boundaries in nanocrystalline materials. [22,33,34] The mobile carriers accumulated or trapped, which affected, and created a localized charge build-up at domain boundaries that acted as carrier trapping/recombination sites. The density of surface states was reduced upon exposure to plasma, making carrier transport more ballistic in the nanoscale walls.…”
Section: Electrical Properties Of the Plasma-treated Filmsmentioning
confidence: 99%
“…[18][19][20] Techniques such as wet chemical passivation and physical layers have been widely employed for surface passivation. [21,22] However, these methods typically lead to the formation of high interfacial capacitance, impeding carrier mobility. Additional post-thermal annealing has been used to overcome the above issues and minimize interfacial capacitance, but this approach raises other technical problems including distortion and collapse of nanoarchitectured voids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation